KOMUNIKASI KANTOR SEBAGAI SARANA PENGEMBANGAN BUDAYA ORGANISASI DI INSTITUSI PENDIDIKAN - Ahmad Salafuddin; Sukemi; Meity Suryandari (STKIP Subang, 2024)
This research explores the role of office communication as a tool for developing organizational culture within educational institutions. Effective office communication, both formal and informal, serves as a mechanism for disseminating information, building relationships, and aligning organizational vision and mission. The study finds that open and transparent communication enhances trust between leadership and staff, strengthens cohesion among members, and reduces potential conflicts. Constructive feedback through communication also contributes to the professional development of educators, ultimately impacting the quality of education provided. However, challenges such as perception differences and communication skills deficits need to be addressed through appropriate communication technologies and enhanced interpersonal skills. Overall, effective office communication is fundamental in creating a harmonious, productive, and adaptive work environment, supporting the achievement of educational institution goals. Keywords: Office Communication, Organizational Culture, Educational Institutions, Interpersonal Skills;